Introduction to quantum information science - Vedral, Vlatko (Oxford Oxford University Press, 2010)
In addition to treating quantum communication, entanglement and algorithms, this book also addresses a number of miscellaneous topics, such as Maxwell's demon, Landauer's erasure, the Bekenstein bound and Caratheodory's treatment of the Second law of thermodyanmics.
Electronic reproduction.
Keywords: Quantum theory; Quantum communication; Science -- Physics -- Quantum Theory